Ecological Problems Of Water Bodies (Eurasian Scientific Herald, 2024)
pollution of the catchment basins with waste water causes the origin and spread of various infectious diseases among the population. Especiallytyphoid fever, paratyphus, salmonellosis, gonorrhea, viral hepatitis "A" type, cholera, etc. Acute infectious diseases are characterized by rapid and massive spread through contaminated water. During the monitoring year, the total number of samples taken from the 2nd category water bodies was 1881 (100%), of which 307 (16.3%) did not meet hygienic requirements. If we analyze the results of the inspection of the water of both water bodies, in the observation year, the water quality indicators of the water bodies of the 2nd category are more polluted than the water quality of the water bodies of the 1st category.